TRANSLATION TECHNIQUES OF DIRECTIVE SPEECH ACTS OF THE MAIN CHARACTERS IN THE PEARL HARBOR MOVIE - Naily Faizati; Achmad Basari (Universitas Samudra, 2021)
This study is entitled ‘Translation Techniques of Directive Speech Acts of the Main Characters in the Pearl Harbor Movie’. This study focuses on analyzing and identifying directive speech acts and the translation techniques used in translating the utterances spoken by the main characters of the Pearl Harbor movie with Indonesian subtitles. This study used the descriptive qualitative method. The source language of the data is English and the target language is Indonesian. The theory employed to analyze the data are taken from translation techniques by Molina and Albir (2002) and directive speech acts theory from Searle in Huang (2007). The researchers found 92 directive speech acts performed by the main characters and 93 translation techniques used to translate each type of directive speech acts. It happens since one directive speech act found in an utterance has to employ more than one translation technique. Based on the results of data analysis, the dominant translation technique used to translate directive speech acts in the Pearl Harbor movie is the literal translation technique. The literal translation technique is used to translate an utterance or expression word for word. The so-called Literal translation technique is dominantly employed due to the findings that a large number of utterances in the source language are translated literally or word for word in the target language. The structural forms of the source language are completely preserved in the target language’s. Meanwhile the least-used techniques are borrowing and discursive creation with only one datum each. It happens because almost every lexical unit of the directive utterances by the main characters in the movie is translatable and predictable in the target language. Keywords: directive speech acts; main characters; Pearl Harbor movie; translation techniques; subtitle